2012
DOI: 10.7869/tg.2012.66
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory and anti-inflammatory cytokine response in diarrhoea-predominant Irritable bowel syndrome patients

Abstract: Background and aim: Irritable bowel syndrome (IBS) is referred to as a functional bowel disorder which is diagnosed by a number of characteristic symptoms (Rome II criteria) in the absence of detectable structural abnormalities. Low-grade inflammation of the intestine may be one of the reasons for development of diarrhoea-predominant IBS (IBS-D). We undertook this study to estimate the serum levels of pro-inflammatory (IL-6, TNF-α) and anti-inflammatory (IL-10) cytokines in IBS-D patients. Methods: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 41 publications
5
56
2
1
Order By: Relevance
“…Several investigators have reported reduced levels of serum anti-inflammatory cytokine IL-10 12,13 or no difference between those with IBS and controls. 14 The aim of the current study is to determine whether measures such as nighttime ANS balance, lactulose/mannitol ratio (intestinal permeability measure), and serum IL-10, identified in the literature as potential markers in IBS, are predictive of outcomes with a cognitively-focused behavioral therapy. Based on the literature, we hypothesized that those IBS patients with lower HRV, higher salivary cortisol, and higher IL-10 levels would show greater improvement with an intervention combining CBT, diet counselling, and education.…”
mentioning
confidence: 99%
“…Several investigators have reported reduced levels of serum anti-inflammatory cytokine IL-10 12,13 or no difference between those with IBS and controls. 14 The aim of the current study is to determine whether measures such as nighttime ANS balance, lactulose/mannitol ratio (intestinal permeability measure), and serum IL-10, identified in the literature as potential markers in IBS, are predictive of outcomes with a cognitively-focused behavioral therapy. Based on the literature, we hypothesized that those IBS patients with lower HRV, higher salivary cortisol, and higher IL-10 levels would show greater improvement with an intervention combining CBT, diet counselling, and education.…”
mentioning
confidence: 99%
“…Studies on circulating or mucosal cytokine levels in IBS patients versus controls had inconsistent results and were not all methodologically comparable. While some of these studies measured the serum/plasma or mucosal levels/expression (Table 2) [17][18][19][20][21][22][23][24][25][26] , others have focused on cytokine production by monocyte or lymphocyte supernatants in the presence or absence of stimulators such as lipopolysaccharides (LPSs) 9,[27][28][29][30] .…”
Section: Cytokines In Ibsmentioning
confidence: 99%
“…The increased level of T-cell activation is consistent with the hypothesis of low-grade immune activation in IBS (Ohman et al 2009 ). Mild infl ammation is involved in diarrhea-predominant IBS patients as proinfl ammatory cytokine TNF-alpha is signifi cantly higher, although no difference in anti-infl ammatory cytokine is observed (Rana et al 2012 ). Although IBS is characterized by the increase of proinfl ammatory cytokines, IL-6 and IL-8, IBS patients with certain extraintestinal comorbid conditions are distinguished by additional elevations in IL-1beta and TNF-alpha (Scully et al 2010 ).…”
Section: Chronic Immune Activation In Infl Ammatory and Functional Bomentioning
confidence: 99%